Evaluasi Usability Pada Aplikasi Banyuwangi Tourism Menggunakan Metode System Usability Scale - Sandi, Arif Wicaksono; Irfansyah, Irfansyah (Visualita Jurnal Online Desain Komunikasi Visual, 2023)
In recent years, Banyuwangi Regency has emerged as one of the areas with rapid tourism development in East Java. The key to the success of tourism development in Banyuwangi cannot be separated from the local government's innovation in managing tourism. One of them is innovation in the digital field by using digital technology in the form of a tourism application called Banyuwangi Tourism. In developing an application, it is necessary to periodically evaluate it to make the application always by user needs. One of the evaluations that can be done in usability evaluation. This article aims to evaluate the usability of the Banyuwangi Tourism application. Usability evaluation is carried out using the System Usability Scale (SUS) method. The data collection instrument used was a questionnaire. The data was obtained in the form of responses from 30 respondents which resulted in an average SUS score of 62. This score indicates that users can accept the Banyuwangi Tourism application based on its usability aspect. However, improving the quality of the application is still needed, because the usability score also shows that the quality of the application is still at grade D. This means that the usability quality of the application is quite good but some improvements are still needed. Evaluation to improve the quality of the application can be started by improving the error and satisfaction aspects of the Banyuwangi Tourism application.